ACCEPTANCE OF A USB-BASED PORTABLE LEARNING RESOURCE ON LOCAL KNOWLEDGE (EXPERIENCE IN THE PHILIPPINES) - Angie R. Jalandoon; Liezel G. Mohillo; Dave E. Marcial (Інформаційні технології і засоби навчання)
Open educational resources (OER) are widely known worldwide, but the Philippines lacks information and implementation compared to other countries. Changes in educational strategies are unavoidable and have an impact on the acceptance of users with new technology. A USB-based Learning Resource, the PLR, was developed and tested to cater to users' flexible means of education. This paper is aimed to describe the level of acceptance of the Portable Learning Resource (PLR) as perceived by the respondents. Specifically, this paper provides a descriptive analysis of Portable Learning Resource acceptance among the respondents in terms of performance expectancy, effort expectancy, attitudes toward using Portable Learning Resource, facilitating conditions, self-efficacy, anxiety, and behavioral intention to use Portable Learning Resource. The study's respondents are the 32 randomly selected respondents, a combination of teachers, students, and librarians from different schools and libraries in the Philippines. An adapted and modified instrument was used and conducted online through Google forms. Results show that PLR is a valuable tool for teachers, students, and librarians in terms of their instruction and self-learning. There is evidence that students will embrace PLR as an OER tool for teaching and self-learning. Similarly, teachers and librarians believe that PLR assists them with their instructions and classroom management, and resource dissemination for remote users. Positive acceptance of PLR implies that PLR can manage and facilitate reusing, revision or derivation, remixing and localization, and redistribution of resources, enabling users to remotely transmit learning contents. However, the stakeholders' and administrators’ initiative on the actual implementation and guidance through seminars, orientations, and instructions, as well as support and collaboration on the integration and operation, are necessary for proper and effective utilization of the system. The study concludes that the promotion of the adoption of Portable Learning Resource is necessary. This study recommends enhancing, maximizing, and promoting the PLR as an OER through collaboration with other institutions, administrators, teachers, librarians, and students to gain additional perspectives.